Estudo da correlação entre Posturografia Dinâmica Foam-Laser e plataforma de força no teste de integração sensorial em adultos jovens normais - Loth, Eduardo Alexandre (2007)
One of the most important tasks of the human postural control system is the balance of the body on a small base of support supplied by the feet. The assessment of postural control represents a challenge task, however presents implications of a big value to professionals from different areas like the Otoneurology, Phonoaudiology, Physiotherapy and others. However, its assessment can be carried out through various equipments, among them the Foam-laser Posturografy Dynamic (FLP), that is a method capable of measuring the body variations, in 6 conditions named Organization Sensorial Test (TOS) and still identifying the contribution of each one of the sensorial systems involved on the balance, it has been widely used. The present study has as objective to evaluate the correlation of the results of the postural control assessment in normal young adults, obtained by means of the FLP and the platform of power. For the accomplishment of the study 30 individuals young adults (21,17 ± 1,45 years old) 19 men and 11 women, academics of UFSM s physical education course were invited, which were submitted to the TOS evaluation by mean of the FLP and platform of power simultaneously. The results revealed that there was correlation rate statistically significant among the 6 conditions of the FLP, with area of displacement of the pressure center (CP) registered by the power platform. From of the analyses of the results it can be concludes that Foam-laser Posturografy Dynamic shows strong correlation with the power platform when evaluating postural control.